Silence, Sound, and Music in Anri Salaâ€™s Cinematic Works - Zivitere, Aija Laura (Richtmann Publishing, 2012)
This essay examines the sonic dimension of Anri Salaâ€™s cinematic works by drawing on the theoretical framework outlined byJean-Luc Nancy in his texts on music and image, as well as on Jacques Derridaâ€™s texts on Nancy. Based on the case study exploring thecinematic practices of Anri Sala conducted within a research project on the border phenomena between cinematic visual arts and thecinema, this essay argues that Salaâ€™s works draw attention to the simultaneous expansion of both â€“ the global sonorous space and theglobal visual space. To characterize Salaâ€™s use of the global sonorous space, specific works are discussed in more detail â€“ â€œIntervistaâ€(1998), â€œDammi i coloriâ€ (2003), â€œLÃ kâ€“katâ€ (2004), â€œLong Sorrowâ€ (2005), â€œAfter Three Minutesâ€ (2007) and â€œLe Clashâ€ (2010) â€“ where thesonorous materials extend from languages such as Albanian, Wolof, American English, British English, French and German, to differentkinds of music such as British punk-rock, jazz improvisations by an American saxophonist and an aria from Giacomo Pucciniâ€™s operaâ€œToscaâ€. By analyzing Salaâ€™s innovative practices of using silence, sound and music, this essay aims to create an improved theoreticalframework for understanding current global artistic practices where the sonorous and the visual influence and shape each other.